Integrating Instructional Leadership Principles into Mentoring Programs for Nurse Leaders: A New Perspective [Letter] - Arjanto P; Aditama MHR; Makaruku VK (Journal of Healthcare Leadership)
Paul Arjanto,1 Mint Husen Raya Aditama,2 Vando Kristi Makaruku3 1Department of Educational Management, Pattimura University, Kota Ambon, Indonesia; 2Department of Guidance and Counseling, Manado State University, Kabupaten Minasaha, Indonesia; 3Department of Educational Administration, Pattimura University, Kota Ambon, IndonesiaCorrespondence: Paul Arjanto, Email paul.arjanto@lecturer.unpatti.ac.id